Divergent Hepatic and Adipose Tissue Effects of Kupffer Cell Depletion in a Male Rat Model of Metabolic-Associated Steatohepatitis - Wiszniewski, Morena (2025)
Kupffer cells (KCs) play a pivotal role in the progression of metabolic-associated steatohepatitis (MASH). This study evaluated the impact of short-term KC depletion induced by gadolinium chloride (GdCl3) in a rat model of MASH. The intervention with GdCl3 effectively reduced KC markers CD68 and Clec4f, together with pro-inflammatory cytokines (IL-1β, TNFα, NOS2), without affecting anti-inflammatory markers (IL-10, MRC1). Histologically, GdCl3 reduced hepatocyte ballooning and NAS despite persistent steatosis. KC depletion was associated with decreased oxidative stress markers (TBARS, 3-nitrotyrosine) and antioxidant enzyme activity (SOD, catalase). Additionally, markers of endoplasmic reticulum stress (ATF4, GRP78, CHOP, P58IPK) and apoptosis (BAX/BCL2 ratio, cleaved caspase-3) were diminished. Despite these improvements, GdCl3 had no effect on lipid or glucose metabolism in the liver, associated with persistent elevation of PTP1B expression induced by SRD intake. KC depletion, however, increased FGF21 expression. GdCl3 treatment improved systemic insulin sensitivity and reduced fasting glucose and NEFA serum levels. In white adipose tissue, the treatment decreased adipocyte size, restored insulin signaling, and inhibited lipolysis (ATGL expression) without altering macrophage infiltration (IBA) or thermogenic protein levels (UCP1) in SRD rats. These findings suggest that KC depletion modulates liver-to-adipose tissue crosstalk, potentially through FGF21 signaling, contributing to improved systemic metabolic homeostasis of SRD animals.